Analisis Aspek Kualitas Keberterimaan Frasa Nomina Dalam Majalah “Colours” Garuda Indonesia Dari Bahasa Inggris Ke Bahasa Indonesia - Yoyok Sabar Waluyo; Laelah Fauziah (Politeknik Negeri Jakarta, 2020)
This study is a translation study focused on translation technique and quality especially on acceptability aspect. Linguistic units used to analyze is noun phrases existed in the magazine of “Colours Garuda Indonesia” published on November 2018. This study uses a qualitative descriptive method. Translation technique used refers to Molina&Albir and translation quality assessment uses categories proposed by Nababan, et.als. The study reveals that types of noun phrases mostly found in this study are modification noun phrases. The most commonly translated using established equivalence. The quality aspect of acceptability translation is on the score 2.7 of 3. It means result of translation can be accepted well by the reader of Bahasa Indonesia. Words or phrases translated reader comprehend them well because they are usually used in Bahasa Indonesia.